Photobiomodulation by Led Does Not Alter Muscle Recovery Indicators and Presents Similar Outcomes to Cold-Water Immersion and Active Recovery - Malta, Elvis de Souza; Lira, Fabio Santos de; Machado, Fabiana Andrade; Zago, Anderson Saranz; Amaral, Sandra Lia do; Zagatto, Alessandro Moura (Frontiers in Physiology, 2019)
Purpose: The aim of the present study was to investigate the effectiveness of photobiomodulation therapy (PBMT) on muscle recovery based on inflammation (interleukin-10 [IL-10]; tumor necrosis factor-α [TNFα]), muscle damage markers (creatine kinase [CK]; lactate dehydrogenase), delay onset muscle soreness (DOMS), and countermovement jump performance (CMJ) after two sprint interval training (SIT) sessions (part-I), and to compare this with active recovery (AR) and cold-water immersion (CWI)(part-II). Methods: Part-I was conducted as a double-blind, randomized and placebo-controlled study and part-II as a parallel-group study. Thirty-six men participated in the studies (12 in part-I and 36 in part-II). Volunteers performed two SITs interspaced by 24-h (SIT1 and SIT2). In part-I, after SIT2, PBMT [Total energy delivered: 600J (i.e., 300J per leg in 5 spots; wavelength: 660-850nm] or placebo interventions were performed, while in part-II PBMT, AR (15-min; 50% of the maximal aerobic power), or CWI (10-min; 10°C) were carried out. Blood samples were collected before, and 0.5, 1, 24, 48, and 72-h after, while CMJ and DOMS were measured before, 24, 48, and 72-h, after SIT2. Results: In part-I, there were no interactions between PBMT and placebo conditions for any blood markers (P≥0.313), DOMS (P=0.052), and CMJ (P=0.295). However, an effect of time was found with increases in LDH, CK, and IL-10 (P≤0.043) as well as a decrease in DOMS at 72-h compared with 24-h (P=0.012). In part-II, there were no interactions between the PBMT, AR, and CWI groups for any markers at the same moments (P≥0.189) and for the peak and integral values (P≥0.193), for DOMS (P=0.314) and CMJ (P=0.264). However, an effect of time was found with an increase in CK and IL-10 (P=0.003), while DOMS decreased at 48-h and 72-h compared with 24-h (P=0.001). Conclusion: In summary, PBMT had no effect on inflammation, muscle damage, CMJ performance, or DOMS after two consecutive sprint interval training sessions compared to placebo, CWI, and AR strategies.